PENYELESAIAN SENGKETA ADMINISTRASI PEMILIHAN KEPALA DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2015 TENTANG PEMILIHAN GUBERNUR,BUPATI DAN WALIKOTA (Studi Putusan Sengketa Administrasi Pemilihan Walikota Dan Wakil Walikota Di Panwas Kota Pematangsi - Herdi Munte; Mirza Nasution; Pendastaren Tarigan; Jusmadi Sikumbang (USU LAW JOURNAL, 2017)
ABSTRACT Legal norms of dispute resolution to local election administration has been specified in the legislation where Election Supervisory Body of Province and District/Municipal authorities resolve the dispute whose decision is final and binding. Problems in this study, first, how rationalization of legal norms, whether the decision is final and binding dispute may be canceled and how the settlement method according to the principles and legal norms. The study is a normative juridical deskristif analytical. The results showed that the logical reasoning or rationalization of the legal norms of appropriate dispute resolution never mind good philosophical, juridical, sociological and political based on the principles of Pancasila state law. Supervisory Body of Province and District/City have attributive and absolute authority to examine and decide administrative disputes. The role of the Election Supervisory Body of Province and District/Municipal conduct a complete assessment in terms of both rechtmatigheid (certainty) and doelmatigheid (usefulness). For that it must be credible and competent and consistent on the principle of law to reduce the weaknesses that still exist.   Keywords: Dispute Administration, Adjudication, Final and Binding and Elections